Single-incision laparoscopic surgery with transabdominal postperitoneal approach for synchronous ileocecal and sigmoid cancers: a case report - Li, Junyi; Lin, Ruijie; Tang, Jin; Ye, Pengcheng; Lv, Qijun; Wei, Shoujiang (Frontiers in Oncology, 2026)
Surgical operation is the most commonly used treatment for colorectal cancer, and the treatment of synchronous multiple primary colorectal cancer is also mainly based on surgical operation. Retroperitoneal Approach for total colectomy in minimally invasive treatment of synchronous multiple colon cancer has reported. But concurrent multi-segmental resection for multiple primary colorectal cancers via a single-incision laparoscopic surgery with transabdominal postperitoneal approach has not previously been reported. We would like to share a case of radical resection of ileocecal cancer and sigmoid colon cancer via transabdominal postperitoneal approach under single-incision laparoscopy. A 72-year-old female presented to the clinic with a progressive alteration in bowel habits and stool consistency over the past year, accompanied by fatigue during the preceding month. The diagnoses included ileocecal cancer, sigmoid colon cancer, severe anemia, coronary atherosclerosis and incomplete intestinal obstruction. Blood transfusion was administered to correct the anemic condition. Given the patient’s comorbidities, including severe anemia and coronary atherosclerosis, along with a body mass index of 20.8 kg/m², a single-incision laparoscopic surgery with transabdominal postperitoneal approach was selected.